Assessing and Predicting the Impact of Land Use and Land Cover Change on Groundwater Using Geospatial Techniques: A Case Study of Tabuk, Saudi Arabia - Albalawi, Eman (Curtin University, 2020)
The study assessed the impacts of LULC changes on the groundwater during the period of 1985–2015 in Tabuk, one of the fast-developing cities of the arid environment of Saudi Arabia. The study provided a clear indication that the unsustainable use of groundwater puts Tabuk at high risk of groundwater depletion. The findings of this study can be used to inform water management decision-makers and strengthen water security in the region and country more broadly.